Prevalence of Active Trachoma and Associated Factors in Areka Town, South Ethiopia, 2018 - Melese Menta Alambo; Eyasu Alam Lake; Shimelash Bitew Workie; Addisu Yeshambel Wassie (Interdisciplinary Perspectives on Infectious Diseases)
Background. Globally, 1.2 billion people live in trachoma endemic areas, 40.6 million people are suffering from active trachoma, and 48.5% of the global burden of active trachoma is distributed in five countries including Ethiopia. However, there is no evidence or no conducted survey/research data or document regarding trachoma prevalence in Areka Town. We, therefore, did a study to assess the prevalence of active trachoma and associated factors in Areka Town in South Ethiopia. Methods. A community-based cross-sectional study was employed. A total of 586 children aged 1–9 years were involved. We compiled a structured questionnaire from the relevant literature and pretested before use. A range of data was collected on the sociodemographic, facility, and service-related, and environmental factors. The outcome variable was measured by using frequencies, cross-tabulation, and percent. Multivariate logistic regression was applied to control potential confounders and to identify the predictors. Results. This study revealed that 37.9% of children aged 1–9 years have active trachoma (95% CI: 34%–42%). Households without latrine (AOR = 6.88; 95% CI: 2.13–22.18), openly disposing domestically produced waste (AOR = 4.62; 95% CI: 2.41–8.83), cooking in the same room (AOR = 5.13; 95% CI: 2.21–11.88), and using the cooking room without a window (AOR = 2.28; 95% CI: 1.11–4.69) were more likely to have their children develop active trachoma. Similarly, children with caretakers having inadequate knowledge about trachoma (AOR = 8.10; 95% CI: 2.04–32.17) were more likely to develop active trachoma. However, households consuming more than 20 liters of water per day were 82% (AOR = 0.18; 95% CI: 0.07–0.44) less likely to have their children develop active trachoma while compared to those consuming less than the figure. Conclusions. The prevalence of active trachoma in the children aged 1–9 years in the study area was found to be high, and it is much higher than the WHO elimination threshold.